Piiblialane õppekirjandus usundiõpetuses: mudel analüüsimiseks - Härm, Silja (Usuteaduslik Ajakiri, 2012)
Study Materials about the Bible in the Context of Religious Education: a Model for Analysis The article deals with the issues of study materials in the religious education at school, focusing on the materials about the Bible in the Estonian language. Estonian syllabus of the religious education is analysed using the theoretical frameworks of John Hull and Hans-Georg Ziebertz concerning the aims of religious education. Subsequently, a model is created for evaluation of study materials about the Bible, which includes two parts: a basis for the choice of educational content and the presentation of the educational content. The model takes into account both the general requirements for the study materials as well as features which are specific to the religious education in its contemporary Estonian context. The central issues of the model are as follows: 1. How relevant is the study material in the context of non-confessional religious education? To what extent does the study material meet the requirements of the syllabus? 2. What kind of cultural context is being assumed (whether veritably declared or not)? 3. To what extent does the study material presuppose previous knowledge about the Bible? 4. What are the criteria for selecting Bible stories? What kinds of paradigms are used for interpreting the Bible? Are there any references to the different possible interpretations and are students encouraged to contemplate about the message the stories address them personally? 5. Does the study material refer to the cultural or religious authority of the Bible? Finally, a selection of textbooks and study materials, which have been recently published in Estonia, is analysed according to the model.